KANDUNGAN LOGAM ESENSIAL TEMBAGA (Cu) DI LINGKARAN TAHUN KARANG PORITES LUTEA DARI PERAIRAN CAGAR ALAM PULAU SEMPU MALANG - Luthfi, Oktiyas Muzaky; Rijatmoko, Sigit; Isdianto, Andik; Setyohadi, Daduk; Jauhari, Alfan; Lubis, Ali Arman (Coastal and Marine Resources Research Center, Raja Ali Haji Maritime University, Tanjungpinang, Indonesia, 2017)
Sempu Island is a nature reserve that has fringing reef with percentage of living coral cover almost constant 37% from 2009 to 2016. Coral massive Porites lutea in this area has a growth rate about 1.09 cm/yr. in average and almost similar with others. Coral massive growth rate can be monitor through their skeletal annual banding. They have two type annual banding, low density for slow growth coral skeletal and high density for fast growth rate of coral skeletal. In this banding coral can record any environmental condition such as sea water temperature, tides and heavy metal. The aim of this research was to know the concentration of copper in Sempu Island Nature Reserve in the past used ICP-OES. The result showed that the Cu concentration in P. lutea skeletal band from 2009-2016 were: 5.213; 6.403; 5.825; 6.511; 6.132; 6.403; 6.467; 6.22 mg/kg. The coral skeletal can absorb the pollutant for hundred years, and it will give important information for palaeo environment that can used for climate modelling in the future.